Reasons for the caries decline in Slovenia - Vrbic˘ V (Blackwell Synergy, 2000)
In 1987, 1993 and 1998, nationwide surveys on the prevalence of dental caries were carried out in Slovenia. Sampling and examinations were performed according to WHO standards. The age groups 6, 12, 15, 18, 35–44 and 65 years or older were studied. In each age group, 200 persons or more were examined on each occasion. The results showed that the proportion of caries-free children and adolescents increased considerably over the 12-year period between the first and the last survey (from 6% to 40% for 12-year-olds). In the same period, the mean DMFT values decreased as follows: from 5.1 to 1.8 for 12-year-olds, from 10.2 to 4.3 for 15-year-olds, from 12.9 to 7.0 for 18-years-olds, from 20.5 to 14.7 for 35– 44-year-olds, and from 27.0 to 22.5 for subjects aged 65 years or more. The notable improvement of dental health can be explained by the preventive programmes Key words: dental caries; epidemiology in operation in various periods.